Broken horses eaudiobook A memoir. - Carlile, Brandi (Random House Audio, 2021)
Brandi Carlile was born into a musically gifted, impoverished family on the outskirts of Seattle and grew up in a constant state of change, moving from house to house, trailer to trailer, fourteen times in as many years. Though imperfect in every way, her dysfunctional childhood was as beautiful as it was strange, and as nurturing as it was difficult. At the age of five, Brandi contracted bacterial meningitis, which almost took her life, leaving an indelible mark on her formative years and altering her journey into young adulthood. As an openly gay teenager, Brandi grappled with the tension between her sexuality and her faith when her pastor publicly refused to baptize her on the day of the ceremony. Shockingly, her small town rallied around Brandi in support and set her on a path to salvation where the rest of the misfits and rejects find it: through twisted, joyful, weird, and wonderful music.   In Broken Horses, Brandi Carlile takes readers through the events of her life that shaped her very raw art—from her start at a local singing competition where she performed Elton John’s “Honky Cat” in a bedazzled white polyester suit, to her first break opening for Dave Matthews Band, to many sleepless tours over fifteen years and six studio albums, all while raising two children with her wife, Catherine Shepherd. This hard-won success led her to collaborations with personal heroes like Elton John, Dolly Parton, Mavis Staples, Pearl Jam, Tanya Tucker, and Joni Mitchell, as well as her peers in the supergroup The Highwomen, and ultimately to the Grammy stage, where she converted millions of viewers into instant fans. Evocative and piercingly honest, Broken Horses is at once an examination of faith through the eyes of a person rejected by the church’s basic tenets and a meditation on the moments and lyrics that have shaped the life of a creative mind, a brilliant artist, and a genuine empath on a mission to give back. Carlile recorded new stripped-down, solo renditions of more than 30 of the songs featured in the book, including her own and songs from artists who’ve inspired her, from Dolly Parton to Elton John, Leonard Cohen and more, available exclusively on the audiobook:   “I Don’t Hurt Anymore” by Hank Snow “Coat of Many Colors” by Dolly Parton “Ride on Out” by Brandi Carlile “Honky Cat” by Elton John and Bernie Taupin “Philadelphia” by Neil Young “Happy” by Brandi Carlile “That Year” by Brandi Carlile “Hallelujah” by Leonard Cohen “Eye of the Needle” by Brandi Carlile “Turpentine” by Brandi Carlile “Wasted” by Brandi Carlile “The Story” by Brandi Carlile “Closer to You” by Brandi Carlile “Caroline” by Brandi Carlile “Josephine” by Brandi Carlile “Sugartooth” by Brandi Carlile “Looking Out” by Brandi Carlile “Beginning to Feel the Years” by Brandi Carlile “Love Songs” by Brandi Carlile “I Will” by Brandi Carlile “I Belong to You” by Brandi Carlile “That Wasn’t Me” by Brandi Carlile “The Mother” by Brandi Carlile “The Stranger at My Door” by Brandi Carlile “Heroes and Songs” by Brandi Carlile “Murder in the City” by The Avett Brothers “Party of One” by Brandi Carlile “The Joke” by Brandi Carlile “Hold You Dear” by The Secret...